2018
DOI: 10.28945/4131
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Motivation in the Use of Lecture Behaviors in the Online Classroom

Abstract: Aim/Purpose: Extant research provides conflicting information regarding the role that lecture behaviors play within e-learning lectures. This study sought to understand what role motivation plays in increasing the likelihood that students engage in lecture behaviors in general, and how motivation affects the differing types of lecture behaviors. Background: The growth of online learning has increased the importance of video lectures as a means of delivering content. As with offline lectures, students may find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Past studies have found a positive relationship between motivational belief strategies and learning performance (Kuo et al, 2013;Mikum et al, 2017;Yamada et al, 2016;Fanguy, Costley, Lange, Baldwin, & Han, 2018).…”
Section: Motivational Beliefsmentioning
confidence: 96%
“…Past studies have found a positive relationship between motivational belief strategies and learning performance (Kuo et al, 2013;Mikum et al, 2017;Yamada et al, 2016;Fanguy, Costley, Lange, Baldwin, & Han, 2018).…”
Section: Motivational Beliefsmentioning
confidence: 96%
“…As with more traditional forms of instruction, many e-learning environments rely on lectures as a means of instruction. As lectures are often provided asynchronously in the form of online videos, students have the ability to view videos at their convenience, and may also pause, rewind, fast-forward, or skip ahead (Costley, Fanguy, Baldwin, & Han, 2018). Some research has suggested that a learner's ability to control the flow of information reduces the cognitive demands of note-taking, as students can listen attentively to segments of the video and pause to take notes instead of having to split attention simultaneously between watching the lecture and taking notes (Balfour, 2006;Davis, Connolly, & Linfield, 2009;Marchand, Pearson, & Albon, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, modern online learning environments provide students with the following capabilities that can affect how they take lecture notes: 1) controlling the flow of information during a lecture, 2) increasing the speed of their note-taking, and 3) collaborating with classmates. As many online courses include pre-recorded lecture videos as an instructional component, students are able to exert some measures of control over the pacing of instruction by engaging in lecture viewing strategies such as pausing a lecture video, rewinding it, rewatching it, or skipping ahead (Fanguy et al, 2018). Such learner-controlled pacing of the contents may help to mitigate the substantial cognitive burden placed on students when trying to simultaneously listen, understand, and take notes during a lecture (Balfour, 2006;Davis et al, 2009;Marchand et al, 2014).…”
Section: Research Backgroundmentioning
confidence: 99%
“…In many online learning environments, students are given the opportunity to engage with course instruction asynchronously, viewing pre-recorded online lecture videos at their convenience. When doing so, learners have the ability to control the flow of information from a lecture video by pausing, rewinding, re-watching, and skipping ahead as needed, and such behaviors have been shown to positively affect students' ability to take notes and to understand the topic of the lectures (Bruff et al, 2013;Fanguy et al, 2018;Veletsianos et al, 2016). For these reasons, some lecturers choose to record their live (synchronous) lectures in order to provide them to students as an online supplemental material.…”
Section: Note-taking In Online Learning Environmentsmentioning
confidence: 99%